Pharmacist management of atrial fibrillation in UK primary care: a cross-sectional study - Shahd Al-Arkee; Julie Mason; M. Sayeed Haque; Abdullah Alshehri; Zahraa Jalal (Taylor & Francis Group, 2024)
ABSTRACTBackground Atrial Fibrillation (AF) increases the risk of stroke by a factor of five, leading a significant cost burdens on healthcare system. Pharmacists, especially those based in a primary care environment are well placed to support patients in this therapeutic area.Objectives To assess primary care pharmacists' actual knowledge on the management of AF symptoms and anticoagulation. Furthermore, to investigate the resources used by pharmacists.Methods A cross-sectional study using survey was conducted, targeting UK-based registered pharmacists employed within primary care settings. Quantitative data were analysed utilising descriptive univariate and bivariate statistics.Results 349 pharmacists completed the adapted 19-questions of the pharmacists' knowledge. Out of a maximum of 19 points, the mean score was 14.34 ± 2.2 (75 ± 11.6%). The questionnaire revealed several significant gaps in pharmacists' knowledge. Most of the surveyed pharmacists (62.8%) reported that they used sources of information to support their consultations. Half reported that they used the National Institute for Health and Care Excellence (NICE) guidance (52.4%) and the British National Formulary (BNF) (50.7%).Conclusions Primary care pharmacists are knowledgeable about AF and its management; however, some gaps exist which may require addressing. Although pharmacists use a variety of information resources, it is the traditional resources that remain the most frequently used.